Quality Control of Wood Pallet at CV. Mandiri Jaya to Reduce Product Defects Using Statistical Quality Tools and FMEA Methods - M. Sahrur Romdloni; Moch. Nuruddin (Universitas Islam Raden Rahmat, Malang, 2025)
This research focuses on improving the quality control of wooden pallets at CV Mandiri Jaya to minimize production defects by utilizing Statistical Quality Tools and the Failure Mode and Effect Analysis (FMEA) method. As a company engaged in manufacturing wooden pallets, CV Mandiri Jaya faces challenges in maintaining consistent product quality. The data collected was analyzed using Statistical Quality Tools, which include check sheets, Pareto diagrams, control charts, and fishbone diagrams to identify and propagate defects. The FMEA method was then applied to determine and prioritize the root causes of defects based on the Risk Priority Number (RPN).The findings show that the most frequent defects are top board dimension mismatch, improper stiffening, and wood cracking. By identifying the root causes of these defects, appropriate corrective actions can be proposed. The results showed that the implementation of this method effectively reduced the number of defective products from 26.1% to 19.5%, which means a decrease of 25.3%. In addition, production efficiency was significantly improved.This research provides a practical framework for manufacturing companies to improve their quality control strategies, ensure higher products, and improve competitiveness in the market.